Corrigendum to “Untangling the relatedness among correlations, Part I: Nonparametric approaches to inter-subject correlation analysis at the group level” [Neuroimage (in press)] - Chen, Gang; Shin, Yong Wook; Taylor, Paul A.; Glen, Daniel R.; Reynolds, Richard C.; Israel, Robert B.; Cox, Robert W. (NeuroImage (Orlando, Fla.), 2017)
[...]as before, ISC was computed over the final time series (here, having 406 time points) using 3dTcorrelate in AFNI. All the bootstrap and permutation approaches (SWB, EWB, SWP and EWP) as well as t-tests for ISC were implemented on the newly processed data, as described in Part I. The ISC Toolbox and 3dttest++ were also re-run, and all statistical analyses and comparisons for the experimental data were performed in the same manner as in Part I. The formats of the figures shown here are directly copied from those shown in Figs. 3 and 4 of Part I, utilizing the same format, arrangement, statistical thresholds, etc.